Characterization Analysis of Textured and Diffused Monocrystalline Silicon Wafer - Asrafusjaman Rubel; M. A. Kabir; Masud Rana; Ariful Islam; Md. Shawkut Ali Khan (European Scientific Journal, ESJ, 2021)
This paper focuses on examining the characteristic analysis of the textured and diffused silicon wafer. Characterization performance of the textured and diffused wafer using surface reflection method, sheet resistance method, SEM, and surface photovoltage method is examined. From the SRM result, it is observed that the reflection of the textured wafer is lower than the raw wafer. This means that the textured wafer forms the pyramid structure, which was measured by SEM. Sheet resistance measures the resistivity of the raw wafer and after phosphorous diffusion into the p-type silicon, the wafer are 2.3 Ω-cm and 0.80 Ω-cm respectively. From the sheet resistance results, it is observed that the phosphorus doping is properly done. The Surface Photovoltage (SPV) result shows that minority carrier diffusion length and lifetime for a solar cell is 86.4μm and 2.8 μsec respectively.